2018
DOI: 10.3892/ol.2018.9774
|View full text |Cite
|
Sign up to set email alerts
|

An atlas for clinical target volume definition, including elective nodal irradiation in definitive radiotherapy of biliary cancer

Abstract: Radiotherapy (RT) is a treatment option for advanced biliary tract cancer (BTC), often combined with sequential and/or concurrent chemotherapy. The use of modern RT techniques requires accurate clinical target volume (CTV) definition and delineation. However, guidelines for CTV delineation in BTC are lacking. Therefore, the aim of this study was to propose a computer tomography (CT) atlas for CTV definition of BTC. We previously proposed guidelines to define the nodal CTV (CTV-N) in BTC. In this study, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…Despite the widespread use of adjuvant CRT in BTC, there is no consensus on the appropriate definition of the CTV in this setting . Our previous study reported on the nodal areas of potential geographic error in adjuvant RT for BTC .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Despite the widespread use of adjuvant CRT in BTC, there is no consensus on the appropriate definition of the CTV in this setting . Our previous study reported on the nodal areas of potential geographic error in adjuvant RT for BTC .…”
Section: Discussionmentioning
confidence: 96%
“…Essentially, the overall picture of the pattern of nodal spread emerging from that study seems to correspond well to our findings; however, it lacks important data on the relation between the tumour T‐stage and subsite and the risk of nodal involvement. Our more detailed analysis revealed some meaningful differences and pitfalls, influencing the CTV design: firstly, for IHC, the differences in the pattern of spread between rIHC and l/hIHC result in significant reduction in the CTV for rIHC when compared to that proposed in the atlas—as inclusion of left gastric, lesser curvature and paracardial LNS is not necessary (Fig. ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations